2013
DOI: 10.1007/s10616-013-9615-x
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression of H1C2 monoclonal antibody in NS0 and CHO cells using pFUSE and UCOE expression system

Abstract: From our recent publications, it was found that the deimmunization method (Dharshanan et al. (2012) Sci Res Essays 7:2288–2299) should be applied for the development of humanized anti-C2 monoclonal antibody (H1C2 mAb). However, the overlapping-PCR mutagenesis procedure used to insert the variable regions into cloning vectors was laborious and time-consuming. Additionally, the expression of H1C2 mAb in NS0 cells was low in static culture vessels. Therefore H1C2 mAb was redeveloped by deimmunization method with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In contrast, a decrease in the cellspecific productivity was observed in two of the non-UCOE cell lines. These results are consistent with previous studies, where inclusion of UCOE in the vector construct resulted in higher levels of recombinant protein production [19,21,27,28,30] and improved the transgene expression in hematopoietic stem cells [25,26]. Otte et al compared the effect of different DNA elements, including UCOEs, S/MARs, cHS4 insulator and anti-repressor elements, on protein expression levels [37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, a decrease in the cellspecific productivity was observed in two of the non-UCOE cell lines. These results are consistent with previous studies, where inclusion of UCOE in the vector construct resulted in higher levels of recombinant protein production [19,21,27,28,30] and improved the transgene expression in hematopoietic stem cells [25,26]. Otte et al compared the effect of different DNA elements, including UCOEs, S/MARs, cHS4 insulator and anti-repressor elements, on protein expression levels [37].…”
Section: Discussionsupporting
confidence: 90%
“…Anti-silencing activity was associated with strongly reduced DNA methylation of promoter, which strongly favours its application in PSC-based cell and gene therapy. In CHO and BHK21 cells, UCOE provided a higher level of transgene expression following stable transfection [19,21,[27][28][29] and maintained the stability of protein expression over 100 generations [30]. In this study, a UCOE vector was used in combination with MTX amplification to improve the frequency of positive clones and to achieve a high volumetric recombinant protein production.…”
Section: Introductionmentioning
confidence: 99%
“…Studies so far have shown that in CHO and BHK21 cells, UCOE provided a higher level of transgene expression following stable transfection and maintained the stability of protein expression over 100 generations . Often recombinant protein production in CHO cells is enhanced by amplifying the gene of interest via methrotrexate (MTX) amplification.…”
Section: Introductionmentioning
confidence: 99%
“…With this innovative system (termed IR/MAR-DHFR) CHO cell lines (both DUXB11 and DG44 backgrounds) can be created that produce more recombinant protein and show a degree of enhanced stability over long term culture in comparison with the standard DHFR -/MTX system on its own. Finally, UCOEs have also been utilised within vector designs to enhance the stability of stable CHO clones and also to boost the productivity from stable transfectants pools (Dharshanan et al 2013;Ye et al 2010;Kwaks and Otte 2006). UCOEs are genetic elements isolated from the upstream regions of housekeeper genes and include unmethylated CpG islands and other promoter-associated elements.…”
Section: Strategies To Combat Cell Line Instabilitymentioning
confidence: 99%